Analgesic, anti-inflammatory and acute oral toxicity profile of leaf and bark extracts of Albizia procera - Sangeetha Mani; Chamundeeswari Duraipandian; Saravana Babu Chidambaram (BMC, 2022)
Abstract Background Pain and inflammation are associatory events in cancer, diabetes, cardiovascular diseases, arthritis and other chronic diseases. Corticosteroids, non-steroidal anti-inflammatory drugs exert potential side effects on long term use. This study was aimed to investigate the acute oral toxicity, anti-inflammatory and analgesic activities of leaf and bark extracts of Albizia procera in experimental animal models. Methods Ethyl acetate, ethanol, and hydroalcoholic extracts of Albizia procera (leaf and bark) were subjected for acute oral toxicity, anti-inflammatory and analgesic screening. Carrageenan and cotton pellet granuloma models were used to assess acute and chronic anti-inflammatory effects, respectively. Intraplanar formalin test was used to assess the analgesic activity. Results All the extracts of Albizia procera were found to be well-tolerated up to 2000 mg/kg in female rats. Ethanolic leaf (ETLE) and bark (ETBE) of Albizia procera showed anti-inflammatory actions. But, only ETBE produced significant protection in chronic inflammation and analgesic activity. Conclusion In summary, Albizia procera possess significant anti-inflammatory and analgesic properties. This study adds evidence on the traditional use of Albizia procera plant for treating painful inflammatory disorders.